Proceedings of the 7th International Conference on ICT for Sustainability 2020
DOI: 10.1145/3401335.3401666
|View full text |Cite
|
Sign up to set email alerts
|

Recycling 4.0

Abstract: Resource scarcity is a global challenge, especially in E-mobility. Currently, Electric vehicles (EVs) are considered as an attractive option on a pathway towards low emission mobility. Nevertheless, due to the increasing sales and acceptance of EVs, new challenges arise regarding the scarcity of utilized materials, especially regarding lithium-ion battery systems. Battery production is responsible for the major share of the environmental and economical impacts of the overall EV production. In order to tackle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Low rate of returned batteries (BSC2) [8,30,31] (N = 3) Lack of information sharing of EoL process (BSC3) [31,[35][36][37] (N = 4)…”
Section: Supply-chain Operations and Management (Bsc) Categorymentioning
confidence: 99%
See 4 more Smart Citations
“…Low rate of returned batteries (BSC2) [8,30,31] (N = 3) Lack of information sharing of EoL process (BSC3) [31,[35][36][37] (N = 4)…”
Section: Supply-chain Operations and Management (Bsc) Categorymentioning
confidence: 99%
“…Hsieh et al [46] highlighted that integrating the entire industry chain, including automakers, battery producers, used-car dealers, and recycling companies, was necessary to achieve a circular economy. Subsequently, information technology enabling end-to-end visibility across the supply chain and facilitating coordination among the involved stakeholders is vital to reduce uncertainty and facilitate better planning and response [36]. Garrido-Hidalgo et al [37] further demonstrated that the required information infrastructure is needed to support the effective operation of a circular supply chain.…”
Section: Social (Es) Categorymentioning
confidence: 99%
See 3 more Smart Citations